Not going quietly [videorecording (DVD)] - Bruckman, Nicholas; Bruckman, Nicholas; Booker, Cory; Harris, Kamala, 1964-; Sanders, Bernard (Kino Lorber, 2021)
Profile of Ady Barkan, a lawyer and liberal activist who was diagnosed with amyotrophic lateral sclerosis at age thirty-two.